2013
DOI: 10.1007/s00373-013-1361-5
|View full text |Cite
|
Sign up to set email alerts
|

Abelian Cayley Graphs of Given Degree and Diameter 2 and 3

Abstract: Let CC d,k be the largest possible number of vertices in a cyclic Cayley graph of degree d and diameter k, and let AC d,k be the largest order in an Abelian Cayley graph for given d and k. We show that CC d,2 ≥ 13 36 (d + 2)(d − 4) for any d = 6p − 2 where p is a prime such that p = 13, p ≡ 1 (mod 13), and− 3 where q is a prime power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…In the next section, we extend a result of Vetrík [7] to deduce new lower bounds for L − C (2) and R − C (2). In Section 3, we describe a direct product construction and use it to build large cyclic Cayley graphs of small diameter and arbitrarily large degree.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…In the next section, we extend a result of Vetrík [7] to deduce new lower bounds for L − C (2) and R − C (2). In Section 3, we describe a direct product construction and use it to build large cyclic Cayley graphs of small diameter and arbitrarily large degree.…”
Section: Introductionmentioning
confidence: 69%
“…In this instance, the trivial lower bound on L − C (2) is 1/4 and the trivial upper bound on L + C (2) is 1/2. Vetrík [7] (building on Macbeth,Šiagiová &Širáň [4]) presents a construction that proves that L In this section, we begin by extending this result to yield bounds for L − C (2) and R − C (2). This argument can also be found in Lewis [3].…”
Section: Diameter Bounds For All Large Degreesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional constructions of large Cayley graphs are given in [21,87,88,65,66,89,96,97,98]. Some of them also use combinations of direct and semidirect products of groups (e.g.…”
Section: Cayley Graphsmentioning
confidence: 99%
“…proved in that there is always a prime p such that p[xx0.525,x] for sufficiently large x , we may extend to all sufficiently large integers d , by simply adding more elements into the corresponding generating set; see . Based on a similar approach, in Vetrík showed that CCfalse(d,2false)1336false(d+2false)false(d4false) for any d=6p2, where p is a prime such that p13 and p1(mod13).…”
Section: Introductionmentioning
confidence: 99%